High‐Throughput Screening of Compound Neurotoxicity Using 3D‐Cultured Neural Stem Cells on a 384‐Pillar Plate. Issue 4 (22nd April 2021) - Kang, Soo‐Yeon; Joshi, Pranav; Lee, Moo‐Yeal
Abstract: Assessing the neurotoxicity of test chemicals has typically been performed using two‐dimensionally (2D)‐cultured neuronal cell monolayers and animal models. The in vitro 2D cell models are simple and straightforward compared to animal models, which have the disadvantage of being relatively low throughput, expensive, and time consuming. Despite their extensive use in this area of neurotoxicology research, both models often do not accurately recapitulate human outcomes. To bridge this gap and attempt to better replicate what happens in vivo, three‐dimensionally (3D) cultured neural stem cells (NSCs) encapsulated in hydrogels on a 384‐pillar plate have been developed via miniature 3D bioprinting. This technology allows users to print NSCs on a pillar plate for rapid 3D cell culture as well as high‐throughput compound screening. For this, the 384‐pillar plate with bioprinted NSCs is sandwiched with a standard 384‐well plate with growth medium for 3D culture, allowing researchers to expose the cells to test compounds and stain them with various fluorescent dyes for a suite of high‐content imaging assays, including assays for DNA damage, mitochondrial impairment, cell membrane integrity, intracellular glutathione levels, and apoptosis. After acquiring cell images from an automated fluorescence microscope and extracting fluorescence intensities, researchers can obtain the IC50 value of each compound to evaluate critical parameters in neurotoxicity. Here, we provide a detailed description of protocols for cell printing on a 384‐pillar plate, 3D NSC culture, compound testing, 3D cell staining, and image acquisition and analysis, which altogether will allow researchers to investigate mechanisms of compound neurotoxicity with 3D‐cultured NSCs in a high‐throughput manner. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Three‐dimensional neural stem cell culture on a 384‐pillar plate Basic Protocol 2 : Compound treatment and cell staining Basic Protocol 3 : Image acquisition, processing, and data analysis